2016
DOI: 10.2174/1874205x01610010042
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Caffeine in the Treatment of Parkinson’s Disease

Abstract: Parkinson’s disease [PD] is the second most common neurodegenerative disorder after Alzheimer’s disease, affecting 1% of the population over the age of 55. The underlying neuropathology seen in PD is characterised by progressive loss of dopaminergic neurons in the substantia nigra pars compacta with the presence of Lewy bodies. The Lewy bodies are composed of aggregates of α-synuclein. The motor manifestations of PD include a resting tremor, bradykinesia, and muscle rigidity. Currently there is no cure for PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 120 publications
(136 reference statements)
0
22
0
1
Order By: Relevance
“…Although the results were due to acute effects of caffeine treatment, it would be interesting to see if these pathways are also up-regulated with prolonged exposure to caffeine. If the activation of neuronal connection/development pathways could be observed in a long term treatment model, it might help explain the links between caffeine and improved cognitive performance, as well as suggested protective effects against Alzheimer disease in epidemiological studies 41 – 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the results were due to acute effects of caffeine treatment, it would be interesting to see if these pathways are also up-regulated with prolonged exposure to caffeine. If the activation of neuronal connection/development pathways could be observed in a long term treatment model, it might help explain the links between caffeine and improved cognitive performance, as well as suggested protective effects against Alzheimer disease in epidemiological studies 41 – 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, the pathological rotational behavior in rats was also suggestive of possible depletion of brain dopamine, which parallels to neurodegeneration (Willis and Sandyk, 1993 ). However, given that caffeine was shown to protect neurons (Kolahdouzan and Hamadeh, 2017 ), enhance cognition and physical performance (Cappelletti et al, 2015 ), and that caffeine can reduce aberrant motor symptoms found commonly in parkinsonism (Roshan et al, 2016 ), a more profound mechanism must be present. To this end, suggestions were made that it is in fact the antagonism of A1 A R s that enhances locomotion and provides for central nervous stimulation (by antagonizing the suppressive A1 A R s), and that it is the antagonism of A2A A R s that lead to dopamine receptor sensitization and therefore aggravation of dopamine-related symptoms (Hadfield and Milio, 1989 ; Popoli et al, 1996 ; Górska and Golembiowska, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease (PD), as the second most prevalent degenerative disorder of the central nervous system, currently affects more than 100, 000 individuals worldwide [22][23][24]. Despite extensive preclinical studies in PD animal models, there is still a lack of effective neuroprotective drugs for PD available [25,26].…”
Section: Discussionmentioning
confidence: 99%